Wpływ języka polskiego na rozwój świadomości narodowej młodzieży galicyjskiej w dobie autonomicznej - Zimmermann, Peter (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2017)
After the Austro-Hungarian compromise in 1867 the Galician parliament and provincial administration gained extensive privileges and prerogatives, especially in education. Galicia was the first crownland that had a school council, which was sanctioned already in 1867. After almost a century the ongoing process of Germanization ended as in the following years the majority of German speaking public officials were replaced by Poles and the Polish language became the main administrativ language and the main language of instruction in school. The article describes changes in the school system and shows the role of the Polish language in primary and secondary education during this so-called epoch of Galician autonomy. A comparison of historical documents and memories from schooldays from former Galician school children allows a realistic insight on the role which the Polish language played in the lives of young Galicians. The analysis shows that the Polonisation of the Galician school system effected the development of Polish national consciousness within young Galicians very slowly and not until the beginning of the 20th century.